AKTIVITAS MAKAN BEKANTAN (Nasalis larvatus) DI HUTAN MANGROVE DESA NIPAH PANJANG KECAMATAN BATU AMPAR KALIMANTAN BARAT - Yokassye, Aghisti; Rifanjani, Slamet; muflihati, muflihati (Universitas Tanjungpura, 2019)
Proboscis monkey feeding activity is activity associated with the fulfillment of the energy needed to maintain the viability of the proboscis. Such activity includes search activity feed, feed selection, behavioral feed entering into the mouth, chewing and swallowing followed. Proboscis is the dominant species, which means folivora feed on the leaves, but sometimes also can feed on flowers and fruit on a small scale. The purpose of this study was to record the feeding activity in Mangrove Forest Village proboscis monkeys Nipah Panjang Batu Ampar District of West Kalimantan using focal animal research methods of sampling and analyzed using qualitative descriptive analysis. The results showed proboscis start feeding activity at 05.00 pm with pemuncakan time at 07.00 pm and 15. 00 pm to feeding behavior that is looking for a large tree limb then sat down and took this feed by way of picking and pulling. The position of the male proboscis monkey eating is always the top and back while females move proboscis at the front leading the group movements during foraging. Percentage feeding activity on the proboscis male is larger than the proboscis females is 33% while the proboscis females is 31% while for the type of feed, there are 7 species of plants which feed the proboscis with the plant is the most widely consumed is leafs Keywords: Proboscis Monkey, Feeding Activities, Behavior, Type of Feed, Nipah Panjang